A survey on lifestyle and attitudes on fruit and vegetable consumption and participation in physical activity in a sample of secondary school and university students from Palermo, Western Sicily (Italian Journal of Public Health, 2010)
Background: Fruit and vegetable (F&V) consumption, and physical activity (PA), are thought to be some of the most important protective factors that can improve long-term health quality of life. Many epidemiological studies indicate, in fact, that F&V consumption and PA are health-promoting and are correlated with the beneficial effects and positive outcomes such as preventing some chronic diseases. Evidence, however, indicates that large proportions of adolescents are not consuming the minimum servings of F&V as recommended by experts and a high percentage of them have sedentary habits.Objective and method: The purpose of this research was to investigate knowledge and behaviors in a sample of secondary school, (250), and university students, (200), referred to F&V consumption and PA. The instrument used for the survey was a questionnaire containing 19 items with multiple choice answers. Data were codified, descriptive analysis and ÷2 tests were computed through Openstat and Statistica software.Results: Only 24,2% of the individuals identified welfare as including healthy eating, and this attitude seemed to be associated with the students’ families educational level. Educational level was also positively associated with the awareness of the importance of a healthy diet for well-being and with PA practice. The percentage of students having knowledge of the expert recommendations on PA and eating guidelines about F&V consumption was about one third of the entire population. Students who met the expert recommendation for daily servings of fruit and vegetables were 27,8%, while only 17,8% practiced regular PA. The principal source of information was university/school, (48,0% and 57,0%).Conclusions: Healthy dietary and PA habits are far from the optimal in our sample of students. Because of the importance for the prevention of many diseases and long term health, there is a need for interventions that target the youth and promote correct dietary habits and avoidance of physical inactivity. In particular, F&V intake and PA practice should be implemented by means of educational interventions in opportune settings, especially targeting schools, families and communities.
Keywords: Nutrition; fruit and vegetable consumption; physical activity; life styles; health education